Processus and recessus adhaerentes: giant adherens cell junction systems connect and attract human mesenchymal stem cells - Wuchter, Patrick; Boda-Heggemann, Judit; Straub, Beate Katharina; Grund, Christine; Kuhn, Caecilia; Krause, Ulf; Seckinger, Anja; Ludwig-Peitsch, Wiebke; Spring, Herbert; Ho, Anthony Dick; Franke, Werner (Cell & tissue research, 2007)
Substrate-adherent cultured cells derived from human bone marrow or umbilical cord blood (“mesenchymal stem cells”) are of special interest for regenerative medicine. We report that such cells, which can display considerable heterogeneity with respect to their cytoskeletal protein complement, are often interconnected by special tentacle-like cell processes contacting one or several other cells. These processus adhaerentes, studded with many (usually small) puncta adhaerentia and varying greatly in length (up to more than 400 μm long), either contact each other in the intercellular space (“ET touches”) or insert in a tight-fitting manner into deep plasma membrane invaginations (recessus adhaerentes), thus forming a novel kind of long (up to 50 μm) continuous cuff-like junction (manubria adhaerentia). The cell processes contain an actin microfilament core that is stabilized with ezrin, α-actinin, and myosin and accompanied by microtubules, and their adhering junctions are characterized by a molecular complement comprising the transmembrane glycoproteins N-cadherin and cadherin-11, in combination with the cytoplasmic plaque proteins α- and β-catenin, together with p120ctn, plakoglobin, and afadin. The processes are also highly dynamic and rapidly foreshorten as cell colonies approach a denser state of cell packing. These structures are obviously able to establish cell-cell connections, even over long distances, and can form deep-rooted and tight cell-cell adhesions. The possible relationship to similar cell processes in the embryonic primary mesenchyme and their potential in cell sorting and tissue formation processes in the body are discussed.